Unexpected transformation of dissolved phenols to toxic dicarbonyls by hydroxyl radicals and UV light - Prasse, Carsten (Proc Natl Acad Sci U S A, 2018)
Water treatment systems frequently use strong oxidants or UV light to degrade chemicals that pose human health risks. Unfortunately, these treatments can result in the unintended transformation of organic contaminants into toxic products. We report an unexpected reaction through which exposure of phenolic compounds to hydroxyl radicals (•OH) or UV light results in the formation of toxic α,β-unsaturated enedials and oxoenals. We show that these transformation products damage proteins by reacting with lysine and cysteine moieties. We demonstrate that phenolic compounds react with •OH produced by the increasingly popular UV/hydrogen peroxide (H(2)O(2)) water treatment process or UV light to form toxic enedials and oxoenals. In addition to raising concerns about potential health risks of oxidative water treatment, our findings suggest the potential for formation of these toxic compounds in sunlit surface waters, atmospheric water, and living cells. For the latter, our findings may be particularly relevant to efforts to understand cellular damage caused by in vivo production of reactive oxygen species. In particular, we demonstrate that exposure of the amino acid tyrosine to •OH yields an electrophilic enedial product that undergoes cross-linking reaction with both lysine and cysteine residues.